PERAN DAN TANTANGAN E-COMMERCE SEBAGAI MEDIA AKSELERASI MANAJEMEN RANTAI NILAI PRODUK PERTANIAN (Forum Penelitian Agro Ekonomi, 2022)
E-commerce in Indonesia is growing fast along with the increasing use of the internet. However, e-commerce adoption has many obstacles, such as the low capability of human resources and infrastructure readiness. This writing aims to identify the roles and challenges of e-commerce agricultural products, review the management aspects of e-commerce agricultural products, and formulate recommendations for e-commerce development in Indonesia. The method used for this research is a literature review. E-commerce is a technology meant to cuts the agricultural value chain. However, it has challenges in implementation, namely, non-durable and perishable agricultural products, compatibility of human resources, too many tax regulations, and the quality and diffusion of the internet. The establishment of e-commerce has a social mission: increasing farmers' welfare. It aims to overcome the farmer's problems, namely limited access to the market and finance. Recommendations for using e-commerce as a medium for accelerating value chain management should be conducted through a dimensional approach, namely human resources, natural resources, technology, markets and finance. Its implementation is to increase the ability of human resources to the novelty of science and technology and to optimize the use of natural resources while still paying attention to ecosystem sustainability. The development of science and technology for e-commerce and agricultural products needs to be carried out following market challenges and creating an inclusive financial system.
Keywords: agricultural product; e-commerce; finance; technology; value chain; keuangan; produk pertanian; rantai nilai; teknologi